PERBEDAAN HASIL BELAJAR METODE COOPERATIVE LEARNING MODEL STAD DENGAN METODE DISKUSI KELOMPOK TERHADAP HASIL BELAJAR MATA PELAJARAN STATIKA DAN TEGANGAN - Eikman Julian Mangape; Nira Nasution; R Eka Murtinugraha (Jurnal Pensil : Pendidikan Teknik Sipil, 2012)
The aims of this research is obtaining the empirical data about the difference of learning output of the students using Cooperative Learning Method STAD Model and Group Discussion Method at the vocational school subject: Static and Stress in SMK Negeri 26 Jakarta. The observation time starts from August 2011 until September 2011 The method for this research is using experimental method. The population is generalized to 216 students of SMK Negeri 26 Jakarta majoring in Technical Drawing for Building which samples are limited to the 11th grade students TGB 1 consisted of 36 students as the firstexperimental class, and TGB 2 consisted of 36 students as the second experimental class. The instrument for this research is test results based on the first test consisted of 30 multiple choice problems. Before the instrument is executed, we do the item validity test and reliability test through the problems. Based on the calculation, it displays that 25 instruments are valid and the rest 5 instruments are invalid for the problem test with the reliability index of 0.90. The analytical requirement test is performed using the normality and homogeneity test. The result shows that from those two classes is revealed to be based on the normally distributed population and homogeneous. Besides, the hypothesis test shows the value of 2.72 which is larger than the required value 1.68, so the H0 is rejected which means that the deviation exists. The final result informs that the difference is occurred during the implementation of cooperative learning method STAD model and group discussion method to the learning output at the vocational school subject: Static and Stress in SMKN 26 Jakarta. The conclusion from this research is the cooperative learning method STAD model is moreeffective compares to the group discussion method.